2008
DOI: 10.1016/j.hrthm.2008.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Association of prolonged QRS duration with ventricular tachyarrhythmias and sudden cardiac death in the Multicenter Automatic Defibrillator Implantation Trial II (MADIT-II)

Abstract: OBJECTIVES-We evaluated the prognostic significance of prolonged QRS duration (QRSd) relative to arrhythmic outcomes in medically-and implantable cardioverter-defibrillator (ICD)-treated patients enrolled in the Multicenter Automatic Defibrillator Implantation Trial (MADIT) II.BACKGROUND-There is conflicting literature on the relationship between prolonged QRSd and arrhythmic events, including sudden cardiac death (SCD), in heart failure patients with or without ICDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 23 publications
3
26
0
1
Order By: Relevance
“…While we did find an increased risk of appropriate shocks with increasing time after MI, ICD shocks are a limited surrogate for SCD and all-cause mortality. 17 …”
Section: Discussionmentioning
confidence: 99%
“…While we did find an increased risk of appropriate shocks with increasing time after MI, ICD shocks are a limited surrogate for SCD and all-cause mortality. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Left bundle (but not right bundle) branch block or LV hypertrophy on electrocardiography are associated with a mildly increased risk of SCD (hazard ratio ~1.5 for both). 58,80 In addition, prolonged QRS duration was associated with SCD and ventricular tachyarrhythmias in two large clinical trials, 81,82 and Das et al have suggested that fragmented QRS on electrocardiography is a marker of structural heart disease and predicts SCD. 83 …”
Section: Risk Factors For Scdmentioning
confidence: 99%
“…In the early analysis of the MADIT II study, a wide QRS >150 ms was associated with a more substantial benefit from ICD1 than was a narrow QRS <120 ms. Subsequent studies did not confirm the relation between QRS width and ventricular arrhythmia (VA) occurrence in primary and secondary prevention ICD patients with structural heart disease 2, 3. However, QRS width predicted SCD in medically treated MADIT II heart failure patients 3…”
Section: Introductionmentioning
confidence: 99%